DAMPAK PENYALURAN BANTUAN LANGSUNG TUNAI (BLT) TERHADAP MASYARAKAT MISKIN DI DESA PERAWANG BARAT KECAMATAN TUALANG KABUPATEN SIAK - DIAN MARINI; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine how the impact of cash transfers to the poor in the village of West Perawang , how the distribution of cash transfers were held and anyone who get these cash transfers . The research was conducted in the  village of West Perawang Siak District of tramp . This study used a descriptive quantitative method by using data retrieval poor people who get cash aid in Perawang West Village Head Office , to know clearly who the people who get the BLT . To collect the data of the respondents used the method of direct observation , interviews , documentation , and management of data used for descriptive quantitative method . The government has also tried to solve the existing poverty by creating programs that they deem to reduce poverty . One of the government programs are BLT , BLT is a program created by the government for the welfare of the poor and helped the poor to meet their basic needs , to strengthen the program the President issued Presidential Decree No. 3 of 2008 on the BLT . The results of this study are bahwasannya the community wants this BLT deleted because they were disappointed with the process and the target , the public is also advised BLT should be replaced with other policies that better understand the poor people , not merely maintain the image of the Government alone. Keywords : welfare , poverty , direct cash assistance program